What is computer-based testing washback, how can it be evaluated and how can this support practitioner research?. Issue 9 (21st October 2019) - Johnson, Martin; Shaw, Stuart
ABSTRACT: With the introduction of a new initiative in a teaching and learning environment there is an ethical responsibility to consider whether the impact of the introduction has met its intended goals, and whether it has harmed those who are influenced by it. Technology and infrastructure developments have encouraged a continued growth in the development and introduction of computer-based tests (CBTs) in educational environments. In the educational assessment literature, enquiry into the impact of testing (of all types) is known as 'washback'. This is a reference to the way in which a test might have a range of influences on learners and teachers prior to the test-taking event. This article reviews the literature on CBT washback and outlines a framework for studying its effects as it is introduced into educational contexts. We then outline a research framework that we have developed (based on the literature) that can be used to evaluate CBT washback. We go on to argue that, to fulfil its potential in supporting the development of change, the research framework needs to act as a mediating device that brings together teaching-practitioner and researcher perspectives. The framework that we propose conceptualises the nature of washback in CBT contexts, as well as the research process and the methods required to understand it. This framework provides an element of common ground between practitioners (i.e. teachers who are involved in a CBT development process) and external researchers, and supports collaboration at three distinct levels.